Research of collision detection algorithm based on particle swarm optimization - Shen Xue-li; Zhang Ji-suo (2010 International Conference On Computer Design and Applications, 2010)
This paper presents a particle swarm optimization based on real-time collision detection algorithm, and combines the PSO and the OBB hierarchy bounding box algorithm. OBB algorithm close simply establishes three-dimensional object bounding box. the collision detection problem in the three-dimensional space change into a two-dimensional space optimization process. PSO algorithm can quickly determine the regional intervention of geometric model, and exclude non-interference in the region. Then, further details of the triangle collision detection, and improves real-time collision detection in the virtual system.